Antimicrobial resistance pattern in a tertiary care hospital: An observational study - Saravanan, Revathy (Medknow Publications & Media Pvt Ltd, 2013)
CONTEXT: The number of organisms developing resistance to commonly used antibiotics is increasing among the various generations. The exact national scenario of antimicrobial resistance (AMR) is not known in India owing to the absence of a central monitoring agency. AIMS: The aim of this study is to identify the group of organisms developing resistance, to know the classes of drugs against, which resistance has emerged and to assess the possible factors that can favor the development of AMR so that antibiotic policy can be formulated for the proper and effective use of antibiotics. SETTINGS AND DESIGN: An observational study was conducted for a period of 1 year from August 2011 to July 2012 in a tertiary care hospital in Pondicherry. SUBJECTS AND METHODS: Data regarding culture and sensitivity of the organisms isolated from different sources such as urine, blood, wound swab/pus, stool, sputum and tracheal aspirations were collected from the records of the Microbiology Department. Sample processing, identification of organisms to the genus and/or species level and antimicrobial sensitivity were carried out as per the Clinical and Laboratory Standards Institute guidelines on the 999 samples received. RESULTS: Out of 999 samples, 125 (12.5%) showed significant growth of organisms exhibiting resistance to either single or multiple drugs. Out of 84 (67.2%) in-patients and 41 (32.8%) out-patient samples, Escherichia was the most common organism isolated with a total of 41 (32.8%), followed by Methicillin sensitive Staphylococcus aureus, 26 (20.8%), Klebsiella 25 (20%), Methicillin resistant Staphylococcus aureus 17 (13.6%), Pseudomonas 10 (8%), Proteus 2 (1.6%), 1 (0.8%) each of Citrobacter and Enterococci. Maximum resistance was observed with commonly used first line antimicrobials such as co-trimoxazole, ampicillin, amoxicillin, amoxyclav, fluoroquinolones, third generation cephalosporins and nalidixic acid. Least resistant or highly sensitive were amikacin, nitrofurantoin, gentamycin and doxycycline among the gram-negative bacteria. Macrolides, clindamycin, gentamycin, nitrofurantoin, vancomycin were the most sensitive antimicrobials against the gram-positive bacteria. Lack of knowledge on the consequences of inappropriate use of antibiotics was exhibited by 63% of subjects in our study. CONCLUSIONS: AMR was more with hospital acquired organisms and against commonly used antibiotics that are available since long period. Variation of resistance and sensitivity pattern with time and geographical location is identified. Periodic AMR monitoring and rotation of antibiotics are suggested to restrict further emergence of resistance.